Dysregulated lipid metabolism networks modulate T-cell function in people with relapsing-remitting multiple sclerosis - Martin-Gutierrez, Lucia; Waddington, Kirsty E; Maggio, Annalisa; Coelewij, Leda; Oppong, Alexandra E; Yang, Nina; Adriani, Marsilio; Nytrova, Petra; Farrell, Rachel; Pineda-Torra, Inés; Jury, Elizabeth C (Clinical and experimental immunology, 2024)
Altered cholesterol, oxysterol, sphingolipid, and fatty acid concentrations are reported in blood, cerebrospinal fluid, and brain tissue of people with relapsing-remitting multiple sclerosis (RRMS) and are linked to disease progression and treatment responses. CD4 + T cells are pathogenic in RRMS, and defective T-cell function could be mediated in part by liver X receptors (LXRs)-nuclear receptors that regulate lipid homeostasis and immunity. RNA-sequencing and pathway analysis identified that genes within the 'lipid metabolism' and 'signalling of nuclear receptors' pathways were dysregulated in CD4 + T cells isolated from RRMS patients compared with healthy donors. While LXRB and genes associated with cholesterol metabolism were upregulated, other T-cell LXR-target genes, including genes involved in cellular lipid uptake (inducible degrader of the LDL receptor, IDOL), and the rate-limiting enzyme for glycosphingolipid biosynthesis (UDP-glucosylceramide synthase, UGCG) were downregulated in T cells from patients with RRMS compared to healthy donors. Correspondingly, plasma membrane glycosphingolipids were reduced, and cholesterol levels increased in RRMS CD4 + T cells, an effect partially recapitulated in healthy T cells by in vitro culture with T-cell receptor stimulation in the presence of serum from RRMS patients. Notably, stimulation with LXR-agonist GW3965 normalized membrane cholesterol levels, and reduced proliferation and IL17 cytokine production in RRMS CD4 + T-cells. Thus, LXR-mediated lipid metabolism pathways were dysregulated in T cells from patients with RRMS and could contribute to RRMS pathogenesis. Therapies that modify lipid metabolism could help restore immune cell function.
Keywords: Male; liver X receptor; glykosfingolipidy; jaterní receptor X; Liver X Receptors; Cholesterol; Adult; relabující-remitující roztroušená skleróza; dospělí; mužské pohlaví; Multiple Sclerosis, Relapsing-Remitting; Glycosphingolipids; metabolismus lipidů; multiple sclerosis; CD4 + T cells; lipid rafts; cholesterol; CD4-Positive T-Lymphocytes; lidé; ženské pohlaví; Humans; Lipid Metabolism; Female; lidé středního věku; CD4-pozitivní T-lymfocyty; Middle Aged; lipid metabolism